(untitled) (Research, Society and Development, 2023)
Iron is among water potability standards established by Ministry of Health Ordinance No. 2914/2011, limited to 0.30 mg.L-1, established due to aesthetic problems related to the presence of iron in the water and its taste. Iron oxidation states are Fe+2 and Fe+3, and ferrous ion (Fe+2) is more soluble than ferric (Fe+3), although not toxic substances result in several problems. Public water supply, especially for needy people who do not have the resources to properly treat their homes. The objective of the present work was to investigate the total iron concentration in municipal water supply located in the Riacho Doce neighborhood in the city of Breves (PA). Samples were prepared and analyzed under the same conditions as standard duplicate calibration solutions. Water analyzes were performed by the flame atomic absorption method; thus all samples underwent a pre-treatment procedure for the removal of organic matter, however the results of all samples are outside the quality standards established by the organs. Some are more than 20 times the maximum making water unsuitable for both consumption and home use.